Reactivation of telomerase reverse transcriptase expression in cancer: the role of TERT promoter mutations - Tornesello, Maria Lina; Cerasuolo, Andrea; Starita, Noemy; Amiranda, Sara; Bonelli, Patrizia; Tuccillo, Franca Maria; Buonaguro, Franco M.; Buonaguro, Luigi; Tornesello, Anna Lucia (Frontiers in Cell and Developmental Biology, 2023)
Telomerase activity and telomere elongation are essential conditions for the unlimited proliferation of neoplastic cells. Point mutations in the core promoter region of the telomerase reverse transcriptase (TERT) gene have been found to occur at high frequencies in several tumour types and considered a primary cause of telomerase reactivation in cancer cells. These mutations promote TERT gene expression by multiple mechanisms, including the generation of novel binding sites for nuclear transcription factors, displacement of negative regulators from DNA G-quadruplexes, recruitment of epigenetic activators and disruption of long-range interactions between TERT locus and telomeres. Furthermore, TERT promoter mutations cooperate with TPP1 promoter nucleotide changes to lengthen telomeres and with mutated BRAF and FGFR3 oncoproteins to enhance oncogenic signalling in cancer cells. TERT promoter mutations have been recognized as an early marker of tumour development or a major indicator of poor outcome and reduced patients survival in several cancer types. In this review, we summarize recent findings on the role of TERT promoter mutations, telomerase expression and telomeres elongation in cancer development, their clinical significance and therapeutic opportunities.